Opposing dopaminergic and GABAergic neurons control the duration and persistence of copulation in Drosophila. - Crickmore, M.A.; Vosshall, L.B. (Cell, 2013)
Behavioral persistence is a major factor in determining when and under which circumstances animals will terminate their current activity and transition into more profitable, appropriate, or urgent behavior. We show that, for the first 5 min of copulation in Drosophila, stressful stimuli do not interrupt mating, whereas 10 min later, even minor perturbations are sufficient to terminate copulation. This decline in persistence occurs as the probability of successful mating increases and is promoted by approximately eight sexually dimorphic, GABAergic interneurons of the male abdominal ganglion. When these interneurons were silenced, persistence increased and males copulated far longer than required for successful mating. When these interneurons were stimulated, persistence decreased and copulations were shortened. In contrast, dopaminergic neurons of the ventral nerve cord promote copulation persistence and extend copulation duration. Thus, copulation duration in Drosophila is a product of gradually declining persistence controlled by opposing neuronal populations using conserved neurotransmission systems.